Bring back the Audience: A Discussion of the Lack of Audience Research in the Field of Media Development - Scott, Martin; Dietz, Christoph (Global Media Journal - German Edition, 2016)
This paper strives to highlight the significant lack of audience research in the field of media development and the consequences of this gap – both for project design and policy making – but also for broader efforts to integrate media into governance debates. Whilst this lack of evidence has been noted before, a number of recently published scoping reviews of the relevant literature now enable us to discuss, in detail, the extent and nature of this gap in our knowledge.